Behaviour outcomes in children with epilepsy 1 year after surgical resection of the ventromedial prefrontal cortex. (October 2019) - Stewart, Elizabeth; Abel, Taylor J.; Davidson, Benjamin; Smith, Mary Lou
Abstract: Early damage to the ventromedial prefrontal cortex (VM) has been associated with impaired behavioural functioning in children without epilepsy, yet behaviour in children with epilepsy and VM lesions has not been investigated. The primary aim of this study was to examine behavioural outcomes in children with epilepsy emanating from the VM preoperatively and one year after epilepsy surgery compared to the general population and matched epilepsy controls. Behavioural outcomes were defined as comprising both problems and competencies (i.e. social, school and co-curricular performance). A secondary aim was to examine whether seizure outcome, number of antiepileptic drugs (AEDs), or age at surgery related to behavioural outcomes. Ratings on the Child Behavior Checklist were examined preoperatively and 1 year after surgery for 20 children with epilepsy who had undergone surgical resection of the VM ( N = 10) or temporal lobe (TL, N = 10). VM and TL groups were comparable on Full Scale IQ (40–101), age of seizure onset (0.5–9.0 years), age at surgery (3.1–16.9 years), seizure laterality (5 left in each group), age at assessments, sex (3 female in VM group, 2 female in TL group) and seizure outcome (7 seizure free in VM group, 6 seizure free in TL group). The VM group had significantly elevated behaviour problems (i.e. withdrawn, thought, social and attention problems) and reduced competencies (i.e. social and school) compared to the general population before and after surgery. VM and TL cases did not differ on any behaviour problem scales pre or postoperatively and neither group showed significant change in functioning over time; however, VM patients had significantly lower total competence than TL patients postoperatively. A significant seizure outcome × time interaction was observed: children who were seizure free following surgery (collapsed across surgical site) showed an improvement in total behaviour problems and aggression at 1 year follow-up, whereas children with ongoing seizures showed a deterioration in these domains. In conclusion, VM lesions in children with epilepsy are associated with behavioural problems but their profile does not differ from that of children with temporal lobe epilepsy. These results are consistent with the concept that seizures arise from epileptogenic networks that may affect multiple cortical areas, even when onset is in a focal site. Highlights: Children with epilepsy and VM lesions have more behaviour problems than children without epilepsy. Behaviour problems in children with epilepsy and VM lesions do not differ to children with TL epilepsy. Thus, similar behaviour profiles were observed in children with epilepsy emanating from the VM and TL. Results are consistent with the concept that seizures arise from epileptogenic networks. Seizures may affect multiple cortical areas, even when onset is in a focal site.